Hormonal Control of Somatic Embryo Development from Cultured Cells of Caraway: Interactions of Abscisic Acid, Zeatin, and Gibberellic Acid - Ammirato, Philip V. (1977)
The effects of abscisic acid, zeatin, and gibberellic acid on the development of somatic embryos from cultured cells of caraway (Carum carvi L.) were observed. Somatic embryos complete development on a basal medium without exogenous hormones, but some are subject to developmental abnormalities including malformed cotyledons and accessory embryos. Both zeatin and gibberellic acid, especially in combination, stimulate growth and increase the frequency of aberrant forms. Zeatin causes the formation of multiple shoots, leafy and abnormal cotyledons, and in the dark, enlarged hypocotyls; gibberellic acid effects root elongation, polycotyledony, and some callus formation. In contrast, abscisic acid, at concentrations which do not inhibit embryo maturation, selectively suppresses abnormal proliferations. With abscisic acid, and especially in the dark, a high percentage of embryos complete development with two fleshy cotyledons on unelongated axes free of accessory embryos. In the light, zeatin eliminates abscisic acid inhibition while gibberellic acid only partially counters its effect, promoting elongated radicles and green rather than white cotyledons. In the dark, zeatin in combination with abscisic acid stimulates extensive callusing. Gibberellic acid does not reverse the effects of abscisic acid but rather enhances them and can counter the disruptive effects of zeatin. The results demonstrate that the balance between abscisic acid on the one hand and zeatin and gibberellic acid on the other can effectively control somatic embryo development and either disrupt or ensure normal maturation.